PENGARUH BRAND POSITION TERHADAP KEPUTUSAN KONSUMEN MEMILIH PERGURUAN TINGGI SWASTA DI SULAWESI TENGAH - Abner Hans Dapimoendi (AkMen JURNAL ILMIAH, 2012)
The goal in this penelitiaan are: to determine the effect of Brand position on consumer decision choosing private colleges in Central Sulawesi. The results of the F count used is 17.604 and F tables 2.65 (17.604> 2.65) with significance level 0.000 therefore much smaller probability value of 0.05, then the regression can be used to mempredeksi Brand position or can be said to be jointly influence the consumer decision to choose private colleges. Coefficient of Determination simple as adjusted (R2) / R Square is equal to 0.694 indicates that this means that 69.40% Variable Power Brand position (X) can explain consumer decision variables choosing private colleges (Y). The remaining 30.60% are caused by other variables that are not observed in this study